Proceedings of the 50 Annual Conference of The Israel Society for the Promotion of Classical Studies. (Scripta Classica Israelica, 2023)
The article presents the program schedule for the 50th annual conference of the Israel Society for the Promotion of Classical Studies including classical studies in Israel, conference schedule, and interdisciplinary research.